The FLASHE Study: A Publicly Available Data Resource. (29th May 2020) - Nebeling, Linda; Dwyer, Laura; Oh, April
Abstract: Objectives: The Family Life, Activity, Sun, Health and Eating (FLASHE) survey was conducted in 2014 to collect information on eating, physical activity, sedentary behaviors, and behavioral correlates from a national sample of parent-adolescent dyads in the United States. It is a publicly available data resource which can be used to research questions about psychosocial, generational, household and neighborhood correlates of health behaviors. Methods: Data were collected from dyads of caregivers and their adolescent children (ages 12–17) ( n  = 1072 completed dyads) between April – October 2014. Two surveys for each respondent: one on diet-related behaviors and one on physical activity-related behaviors were collected. An additional 407 dyads wore an accelerometer for seven days and completed an activity log. A 'geoFLASHE' dataset used parent-provided address information for home and school to geocode these locations and compute a set of variables applied to several different neighborhood definitions, including both circular and street-network buggers with distances ranging from 400 – 1200 meters. Accelerometer variables were computed for a subset of adolescents who wore an Actigraph Gt3x+ for seven days and includes estimates from raw and activity counts data. Training webinars on dyadic analytical methods, models and applications were provided. Results: The geoFLASHE dataset includes variables for neighborhood, socioeconomic status factor, factor scores for built environment characteristics (high density, older neighborhood, and short commutes), and other variables for each buffer configuration. The adolescent accelerometer dataset offers summary variables of accelerometer data and minute-level estimates of light, moderate, and vigorous activity using Crouter, Chandler, and GGIR processing methods. Additionally, training webinar, questionnaires, survey data files and codebooks are available. Conclusions: The FLASHE study data resources can be used to understand cancer-related health behaviors in family dyads. Funding Sources: FLASHE study was funded by the National Cancer Institute under contract number HHSN2612012000391 issued to Westat, Inc.